Glutathione system in rat blood serum under the conditions of carrageenan-induced joint inflammation and chondroitin sulfate prophylactic injection - Дворщенко, Катерина Олександрівна; Короткий, Олександр Григорович; Гребіник, Дмитро Миколайович; Торгало, Є. (Київський національний університет імені Тараса Шевченка, 2021)
The goal of this work was the research of chondroitin sulfate prophylactic action on the glutathione system state in rat blood serum during acute joint inflammation. The research was performed on white non-linear pubertal rat males weighting 160-240 grams in compliance to all general ethical principles of animal research. All animals were divided to four experimental groups. The first group – the control: the animals were injected with 0,1 ml of 0,9 % NaCl solution in a right hind leg. The second group – rats were subjected to daily intramuscular injections of 3 mg/kg of chondroitin sulfate in the theurapeutic dose during 28 days. The third group – the animals were subjected to daily doses of 0,1 ml of 0,9 % NaCl solution injected in right hind extremities and starting from 29th day the acute joint inflammation was modelled (the animals were subjected to 0,1 ml of 1% of сarrageenan intramuscular injection in right hind extremities. The fourth group – rats were receiving intramuscular injections of therapeutic dose of 3 mg/kg of chondroitin sulfate for 28 days, and after that the acute joint inflammation was modelled starting from 29th day. 40 animals in all were taking part in the experimental research. The glutathione peroxidase activity was assessed judging from the decrease in GSH amount in the reaction with Ellman reagent. The glutathione peroxidase activity was estimated by the decrease in probe optical density owing to NADPH oxidation. Glutathione transferase activity was estimated by the speed of the conjugate formation between GSH and 1-chloro-2,4-dinitrobemzene. The amount of reduced glutathione was estimated spectrophotometrically using orthophthalic aldehyde. It was established that during the carrageenan-induced inflammation the glutathione peroxidase, glutathione reductase and glutathione reductase activity were reduced, a well as the amount of reduced glutathione, whereas the glutathione transferase activity was increased in comparison to the control. It was shown that under the prophylactic injection of the chondroitin sulfate based preparate to animals with acute joint inflammation the aforementioned parameters were partially stabilized.

Дослідження проведені на білих нелінійних статевозрілих щурах-самцях масою 180–240 г із дотриманням загальних етичних принципів експериментів на тваринах. Усіх тварин розподілено на чотири експериментальні групи. Перша група – контроль: тваринам субплантарно вводили у задню праву кінцівку 0,1 мл 0,9-відсоткового розчину NaCl. Друга група – щурам щоденно протягом 28 діб внутрішньом'язево вводили терапевтичну дозу 3 мг×кг-1 хондроїтин сульфату. Третя група – тваринам щоденно протягом 28 діб внутрішньом'язево в задню праву кінцівку вводили 0,1 мл 0,9-відсоткового розчину NaCl та на 29-й день моделювали гостре запалення суглоба (тваринам субплантарно в задню праву кінцівку вводили 0,1 мл 1-відсоткового розчину каррагінану). Четверта група – щурам щоденно, протягом 28 діб внутрішньом'язево вводили терапевтичну дозу 3 мг×кг-1 хондроїтин сульфату, після чого на 29-й день моделювали гостре запалення суглоба. Загальна кількість тварин, залучених до експериментальних досліджень, становила 40 особин. Глутатіонпероксидазну активність оцінено за зменшенням вмісту GSH у реакції з реактивом Елмана. Глутатіонредуктазну активність виміряно за зменшенням оптичної густини проб внаслідок окиснення НАДФН. Глутатіонтрансферазну активність визначено за швидкістю утворення кон'югату GSH з 1-хлор-2,4-динітробензолом. Уміст відновленого глутатіону виміряно спектрофлуориметрично з використанням ортофталевого альдегіду. Встановлено, що за каррагінан-індукованого запалення суглоба в сироватці крові знижувалася глутатіонпероксидазна, глутатіонредуктазна активності й уміст відновленого глутатіону, водночас зростала глутатіонтрансферазна активність порівняно з контролем. Показано, що за профілактичного введення препарату на основі хондроїтин сульфату тваринам із гострим запаленням суглоба вищезазначені показники частково відновлювалися.
Глутатіонова система в сироватці крові щурів за умов каррагінан-індукованого запалення суглоба та профілактичного введення хондроїтин сульфату
Keywords: гостре запалення суглобу; хондроїтин сульфат; глутатіонова система; сироватка крові; acute joint inflammation; chondroitin sulfate; glutathione system; blood serum.